Simple 3D culture of dissociated kidney mesenchyme mimics nephron progenitor niche and facilitates nephrogenesis Wnt-independently - Dapkunas, Arvydas (Sci Rep, 2019)
Kidney mesenchyme (KM) and nephron progenitors (NPs) depend on WNT activity, and their culture in vitro requires extensive repertoire of recombinant proteins and chemicals. Here we established a robust, simple culture of mouse KM using a combination of 3D Matrigel and growth media supplemented with Fibroblast Growth Factor 2 (FGF2) and Src inhibitor PP2. This allows dissociated KM to spontaneously self-organize into spheres. To reassess the requirement of WNT activity in KM self-organization and NPs maintenance, cells were cultured with short pulse of high-dose GSK3β inhibitor BIO, on a constant low-dose or without BIO. Robust proliferation at 48 hours and differentiation at 1 week were observed in cultures with high BIO pulse. Importantly, dissociated KM cultured without BIO, similarly to that exposed to constant low dose of BIO, maintained NPs up to one week and spontaneously differentiated into nephron tubules at 3 weeks of culture. Our results show that KM is maintained and induced to differentiate in a simple culture system. They also imply that GSK3β/WNT-independent pathways contribute to the maintenance and induction of mouse KM. The robust and easy 3D culture enables further characterization of NPs, and may facilitate disease modeling when applied to human cells.